Arco del conocimiento Introducción a la historia y metodología de la ciencia - OLDROYD, David (CRITICA, 1993)
Contiene: PLATON; ARISTOTELES; GALILEO, Galilei; BACON; HOOKE; DESCARTES, René; NEWTON; LOCKE; LEIBNIZ; BERKELEY; HUME; KANT; COMTE; RUSSELL; WITTGENSTEIN; REICHENBACH; EINSTEIN, Albert; CAMPBELL; KUHN; LAKATOS, Imre; FEYERABEND, Paul K.